2007
DOI: 10.1007/s11064-006-9242-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Tau Expression in Transgenic Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: The work is a continuation of studies on tau expression and alternative splicing in the central nervous system of transgenic mice harboring human SOD1 with G93A amyotrophic lateral sclerosis (ALS)-associated mutation. Since age is an important risk factor for ALS, we expanded the studies into younger animals (age 5 and 25 days). We also included cerebellum, a structure not studied in the context of neurodegeneration in ALS. We found decreased total tau-mRNA expression in hippocampus but not in cortex and spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, growing evidence indicates the presence of functional changes in this structure in the course of ALS, including increased activations of areas involved in motor learning, among which basal ganglia and the cerebellum [38]. In our earlier studies of tau mRNA expressions in the cerebellum of SOD1G93A mice, we observed its very high increase at both presymptomatic and symptomatic stages, which was an opposite finding compared to the changes observed in the frontal cortex and spinal cord, the structures stereotypically involved in ALS pathogenesis [28,39]. It is possible that the kinesin expression is downregulated in response to increased tau expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, growing evidence indicates the presence of functional changes in this structure in the course of ALS, including increased activations of areas involved in motor learning, among which basal ganglia and the cerebellum [38]. In our earlier studies of tau mRNA expressions in the cerebellum of SOD1G93A mice, we observed its very high increase at both presymptomatic and symptomatic stages, which was an opposite finding compared to the changes observed in the frontal cortex and spinal cord, the structures stereotypically involved in ALS pathogenesis [28,39]. It is possible that the kinesin expression is downregulated in response to increased tau expression.…”
Section: Discussionmentioning
confidence: 99%
“…The changes were prominent in frontal cortex, but not in hippocampus and spinal cord. In frontal cortex at symptomatic stage of the disease, the level of total tau mRNA was decreased by about 20%, mainly because of 2 N isoform down-regulation [26, 40]. In the present studies conducted on B6-C3H hybrids with the SOD1G93A mutation (SOD1/+) the total tau expression in frontal cortex at symptomatic stage was even lower (decreased by more than 60%) and the level of all isoforms was decreased, but especially that of 2 N (a threefold decrease).…”
Section: Discussionmentioning
confidence: 99%
“…The present results are with agreement with our earlier studies conducted on SOD1G93A mice (which were not hybrids with C3H). We have shown that the level of total tau-mRNA increases in cerebellum already in newborns (by 25%) and it further rises with age reaching the highest value at symptomatic stage (by 40%) due to enhance of all isoforms expression [40]. Cerebellum is the structure usually not studied in motor neuron diseases since cerebellar dysfunction is not a clinical feature of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…In SOD1-G93A Tg mice model for ALS ( SOD1 G93A ). The most prominent alterations of tau expression were reported in the cerebellum (Baranczyk-Kuzma et al, 2007). …”
Section: Introductionmentioning
confidence: 99%